Creating and Weighting Hunspell Dictionariesas Finite-State Automata - Pirinen, Tommi; Lindén, Krister (Investigationes Linguisticae, 2010)
Therearenumerousformatsforwritingspell-checkersforopen-source systems and there are many lexical descriptions for natural languages written in these formats. In this paper, we demonstrate a method for converting Hunspell and related spell-checking lexicons into ﬁnite-state automata. We also present a simple way to apply unigram corpus training in order to improve the spellcheckingsuggestionmechanismusingweightedﬁnite-statetechnology.Whatwe propose is a generic and efﬁcient language-independent framework of weighted ﬁnite-stateautomataforspell checkingintypicalopen-sourcesoftware,e.g.Mozilla Firefox, OpenOfﬁce and the Gnome desktop.